10. QUALITY OF LIFE IN TERMS OF VISUAL FUNCTION OF DIABETIC PATIENTS AT E HOSPITAL IN 2020 (Vietnam Journal of Community Medicine, 2023)
Objective: To assess the quality of life-related to vision among diabetic patients at E Hospital and explore associated factors. Methods: A descriptive cross-sectional study was conducted, analyzing data from 119 diabetic patients who received management and treatment at E Hospital in 2020. Results: The average score for vision-related quality of life, as measured by NEI-VFQ-25, was 83.25 ± 13.35 points. Among the aspects evaluated, dependence on others received the highest score of 94.46 ± 13.03 points, while the overall health aspect achieved the lowest mean score of 37.39 ± 17.78 points. Older age, female gender, and urban residence were demographic factors significantly associated with the lower vision-related quality of life (p
Keywords: Vision-related quality of life, diabetes, NEI-VFQ-25.